La teoría pura del derecho : un recorrido panteísta hacia la superación del dualismo estado y derecho - Lerose, María Regina (2018)
This paper provides a brief overview of Hans Kelsen critiques of the State as a metaphorical personification of the law. It will also show the need to deconstruct those mythological dualisms that prevent the formation of pure science, free of ideologies, policies or any aspect that are not normative and exceeds the object of study: the law. This journey towards the overcoming of State/Law dualism and the sense of unity that the author will stablish in several studies, could be a way of expressing juridical pantheism, an issue that will be analyzed through one of his best-known disciples, as Luis Legaz y Lacambra.